The Impact of Supporting Industries on Attracting Foreign Direct Investment: A Case Study in Vinh Phuc Province, Vietnam - THUY, DO THI THU; HOANG, LE DUC; ANH, LE QUOC (The journal of contemporary issues in business and government, 2021)
Summary: This study focuses on explaining the theoretical basis of the impact of supporting industries (SI) on attracting foreign direct investment (FDI); assessing the state of the impact of SI on FDI attraction into Vietnam in general and Vinh Phuc province in particular. Quantitative analysis results show that, in the field of SI in Vietnam, import suppliers are dominating domestic suppliers, the factor that most affects FDI enterprises' satisfaction level is labor, especially hard-work and progressiveness, followed by quality and attitude of discipline compliance of labor resources. The domestic SI still face difficulties in approaching customers, quality assurance, with outdated technology, lack of high-tech manpower, poor innovative research capabilities... In the coming time, to contribute to FDI attraction into Vietnam, to become a supplier for FDI enterprises, domestic enterprises working in supporting industries (SI enterprises) need to increase the rate of capital investment on technology, improve the quality of human resources, and promote information exchange with FDI enterprises.